FETAL DISTAL EXTRADACTYLY (CLINICAL CASE) - Elgina, Svetlana Ivanovna; Grishkevich, Elena Valentinovna; Rudaeva, Elena Vladimirovna; Moses, Kira Borisovna; Moses, Vadim Gelievich; Rudaeva, Elena Germanovna (Mother and Baby in Kuzbass, 2026)
Ectrodactyly is a heterogeneous group of congenital malformations (CMF) characterized by reductional defects of fingers of hands and/or feet. The defect can vary from insignificant hypoplasia of phalanges to complete absence of fingers with splitting of the hand or foot into two parts According to domestic and foreign statistics, the incidence rate is from 0.1 to 1.94 cases per 1000 newborns. The etiology is associated with genetic mutations (the most common mutations are of the TP63 gene, as well as duplications of the SHFM loci) and teratogenic factors affecting the embryo at critical times (3-7 weeks of gestation).The presented clinical case of distal ectrodactyly in a newborn highlights the importance of careful assessment of limb anatomy during ultrasound screening. Patients with a burdened medical history (the presence of ER in the past) require expert ultrasound with an emphasis on visualization of the distal extremities in the second and third trimesters.
Keywords: fetal malformation; ultrasound diagnostics; perinatal outcome; prenatal diagnostics